Sustainable mobility in Lyon: should we hang private car drivers? - Buhler, Thomas (TeMA - Journal of Land Use, Mobility and Environment, 2010)
Incriminated for negative externalities such as both local and global pollution, noise, sealing extension or public space high consumption, private cars have been perceived as a factor of un-sustainable mobility since the early 80’s by urban planners and designers. In the new paradigm of the so-called “sustainable city” urban planners and designers target now a modification of social behaviour and particularly social mobility practices. The production of transport alternatives and restrictions to automobiles in city centres through car-parking limitations and fare systems as developed in urban mobility plans (Plans de Déplacements Urbains) are unfortunately too weak to generate a modal shift ripple-effect in French cities. Considering the last issue of the French national institute of statistics and economic studies’ survey (Hubert, 2009) the modal-share in favour of car-transit remains the same for the period of time between 1994 and 2008 for the biggest French cities, in spite of steady efforts for the development of public transportation alternatives such as the diffusion of the tramway’s comeback (from Grenoble 1986, to Dijon 2013). According to a series of relatively recent research papers (Kaufmann, 2002 ; Lefevre & Offner, 1990) focused on the “economically irrational” behaviour of the majority of private-car drivers concerning the question of modal shift, a research framework has been developed. This frameworks specially focuses on the disconnect between the rationalities of resistant car-driver’s social mobility practices in the metropolitan space, compared to the rationale of urban mobility masterplans has, assuming that user’s “tactics” answer planner’s “strategies” (De Certeau, 1990). This approach of identifying this disconnect between rationalities in planning and rationalities in social practices in the urban mobility context is aimed to extend to the complex perception of urban environments by car-drivers, to identify new targets of modal-split policies to be structured as new action-levers. This perception will deal with several issues orchestrated through urban design projects such as public spaces, physical distances or parking constraints. The second main issue of this conceptual framework deals with rationalities of user’s mobility practices. The axiological rationality (Boudon, 1995) seems to be heuristic to question values and practices, searching for the rationale behind the conclusions that users draw when making mobility decisions (for example “the car is faster in my situation”). This justification process needs to be finely analyzed in combination with several concepts, norms and values that “make sense” for the individual. We propose the hypothesis that the combination of perception biases and axiological rationalities could helps to explain behaviors defined as “irrational” for urban mobility planners and to delineate the major levers of social acceptation and adoption of so-called sustainable urban environments.